The Effect of Physical Activity on Hypertension on Adults: Meta Analysis - Dyah Mubarokah Ahadiyati; Didik Gunawan Tamtomo; Vitri Widyaningsih (Masters Program in Public Health, 2020)
Background: Physical activity has an influ